Hans Neumann 60 år - Glob, P. V. (Kuml, 1968)
HANS NEUMANN 60 YEARS Hans Neumann was among the first university-trained archaeologists to become curator of a provincial museum. When he was appointed curator of the Haderslev Amtsmuseum in 1936, after 3 years as an assistant at the National Museum, there were only few museums outside Copenhagen with professional curators. Haderslev Amt is a large county and one of the richest archaeological areas in Denmark, and Hans Neumann has had to cover it alone. In recent years his responsibility has been extended to the whole of South Jutland. The fact that he has nevertheless been able not only to carry out a full programme of work in the field, but to build up one of the best prehistoric collections in the country is due to his enormous energy and to the local support he has enjoyed in his county of birth. Hans Neumann’s working days have always been long, shared equally between excavation and work in the museum. At the same time, he has published his results in innumerable lectures and articles in the press and archaeological journals. Of his many important finds, only one of his latest will be mentioned here, the splendid weapon offering in EjsbøI bog, the excavation of which he and Mogens Ørsnes of the National Museum have directed for 8 years. Prior to this collaboration lay many years of solitary activity far from the nearest colleague, punctuated only by short and infrequent visits from the National Museum, which were his only opportunity to discuss scientific and museum problems. In spite of this isolation, Hans Neumann has retained his sense of humour and has worked so successfully, that the big museum in Haderslev can no longer house the collection. He has won such respect for the museum, however, that the local authorities have approved his plans for an extension to more than twice the size of the present museum. It is characteristic of Hans Neumann that he shows great consideration for visitors to the museum. A lecture hall, study rooms and cafeteria are included in the new buildings, and a hall for temporary exhibitions ranging from archaeology to modem art, so wide are his interests. The completion of these plans for the museum will be a great benefit to archaeology in Jutland and a fine monument to Hans Neumann’s life’s work. P. V. Glob